The Anxiety of Theodore Finch as Seen in All The Bright Places The Movie - Cantika Asmara Puspitaningrum, Niken; Edi Pramono, Robert (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
Anxiety is still a frequent occurrence in the lives of many people that interferes with mental health to this day. This is what allows anxiety to occur. The purpose of this study is to analyse the types of anxiety that Finch suffers from and the impact of anxiety on Finch's life in the film All The Bright Places. The data collected in this thesis comes from cinema, research articles and journals. The theory used is the Anxiety Nevid theory in Abnormal Psychology, which can analyse the overall anxiety disorder of the main character. The results of the analysis of this study are: the types of anxiety that Finch suffers from are Phobia Disorder, Obsessive Compulsive Disorder, General Anxiety Disorder and Panic Disorder. This anxiety affects all of Finch's life activities and mental health. The impact of anxiety causes Finch to experience depression and end his life by committing suicide.